Implementasi Project Based Learning Berbasis Deep Learning dalam Mengembangkan Berpikir Kritis Menulis Teks Deskripsi - Tashilun Neli Amali; Muhammad Masykur Baiquni (Lingua Franca, 2026)
This study aims to analyze the acceleration of critical thinking skills among 7th-grade students at SMP Islam Gedangan in writing descriptive texts through a Project-Based Learning (PjBL) model integrated with Deep Learning. A qualitative case study approach involving 17 students was employed. Data were collected through observation, interviews, and written work, and were analyzed using the SOLO Taxonomy framework. The research findings reveal a significant cognitive transformation. Before the intervention, 82.35% of students exhibited a “surface learning” pattern—predominantly at the multi-structural level (70.6%)—due to issues such as copy-pasting and group passivity. Following the intervention, there was a marked shift toward “deep learning” (76.5%), with 35.3% of students reaching the highest level (Extended Abstract). Students demonstrated the ability to write critically—moving beyond the concrete text—by integrating deep personal reflection and insights. This cognitive transition was driven by the application of “meaningful,” “mindful,” and “joyful” pillars, which effectively activated the students’ metacognitive awareness. The study concludes that integrating Deep Learning-based Project-Based Learning (PjBL) effectively restructures students’ mindsets from a linear, fragmented approach to an integrative, conceptual one in language learning.